Unearthing Mythological Legends of Local Communities in Pontevedra, Capiz, Philippines - Rossandrew Banico-Villaruel (Philippine Association of Institutions for Research, Inc., 2014)
The mythological origin of a place does not literally tell us where we are or who we are, they can be clues to understand the significant stories of history of a place it may be in the form of words and phrases used by the first inhabitants and speaking of the things that they saw, experienced and heard in the world around them. The study was conducted to unearth the mythological legends of different local communities in the municipality of Pontevedra, Capiz. The study used a qualitative-historical-ethnographic research designs and data were gathered through interview. The results revealed that out of 26 local communities in the municipality of Pontevedra, Capiz, Philippines, there were seven local communities with two legends. Most legends were classified as allegorical and philological theories; each legend has legendary root; one local community legend has relevance to its festival celebration; 15 local community legends have relevance to its topographical location and 10local community legends are relevant to the livelihood of the people. The names of every local community can be traced to its own legend, has etymological root and do not show relevance to their festival celebrations. The researcher recommended the use of locally produced literary materials in reading centers for the preservation of historical and cultural aspect of the municipality.